INOVASI TEKNOLOGI DAN DAMPAKNYA TERHADAP MANAJEMEN BUDGETING DI INSTITUSI PERBANKAN - Anwar, Saeful; Huzaimah (Politeknik Negeri Medan, 2025)
This study explores the impact of technological innovation on budgeting management in banking institutions. In the digital era, the development of information and communication technology has brought significant changes in the way banks operate and plan budgets. Through a literature study approach, this study identifies various technological innovations, such as cloud-based data management systems, big data analytics, and process automation, which have improved efficiency, accuracy, and transparency in the budgeting process. Although these innovations offer many benefits, challenges such as data security, employee training needs, and changes in organizational culture remain major concerns. This study concludes that in order to optimally utilize technology, banking institutions need to develop a comprehensive strategy that focuses not only on the application of technology, but also on managerial aspects and organizational culture.